Pemanfaatan Limbah Tempurung Kelapa sebagai Media Bahan Bakar Alternatif Berbentuk Briket Desa Siwalan Kecamatan Panceng Gresik - Nikmah, Nafidatun; Musbikhin, Musbikhin; Safikah, Nurul (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2023)
Coconut shells are solid waste from processed coconuts from which the coconut meat has been removed, but there are still many people who don't know how to manage them, so they become waste. Thus, the author is interested in managing this waste into something that has selling value so that apart from reducing the waste population it can also improve the economy. The author took a case study in Siwalan village, Panceng sub-district, Gresik Regency, because this area has quite a lot of coconut shell waste. The method used to implement this program is the Asset Based Community Development (ABCD) approach, by providing education and outreach to the community, especially mothers and traders, about how to process coconut shells into briquettes. This implementation method involves collecting coconut shells, processing, printing and drying and packaging. Through this activity, young people and other community groups will learn about how to make simple alternative energy which is not only a solution to waste problems, but also opens up business opportunities that can advance the village economy.